1981
DOI: 10.1021/jo00332a042
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic amines from carboxylic acids and ammonia. A homogeneous catalytic process

Abstract: Purification of the surfactant has been described.9 Sodium salts were used for the buffers.Kinetics. The formation of o-nitrophenoxide ion at 25.0 °C was followed at 405 nm, using a Gilford spectrometer for the slower reactions and a Durrum stopped flow spectrometer for the faster reactions. The pH of the buffered solutions was measured in the absence of surfactant. The first-order rate constants, are in reciprocal seconds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…An early report on the amination of benzoic acid was disclosed by Arzoumanidis and Rauch in 1973 . They showed that the reaction of copper benzoates with ammonia at a high temperature and pressure provides aniline with concominant decarboxylation.…”
Section: C(sp2)–h Functionalizationmentioning
confidence: 99%
“…An early report on the amination of benzoic acid was disclosed by Arzoumanidis and Rauch in 1973 . They showed that the reaction of copper benzoates with ammonia at a high temperature and pressure provides aniline with concominant decarboxylation.…”
Section: C(sp2)–h Functionalizationmentioning
confidence: 99%
“…It was then reported that Cu II benzoates react with ammonia at high pressures and temperatures to give anilines with concomitant protodecarboxylation. However, Arzoumanidis and Rauch later highlighted the limitations of this catalytic methodology, namely low yields coupled with the formation of multiple products and the necessity to use harsh conditions (Scheme ) . These two reports nonetheless remain the only examples of the use of a carboxylic acid as a traceless directing group for C−N bond formation.…”
Section: C−n Bond Formationmentioning
confidence: 99%
“…Moreover, the synthesis of diarylamine derivatives of anthranilic acids is unknown via this carboxylate‐directed strategy and access to N ‐alkyl anthranilic acids was provided only through the use of cyclic chloramines. Finally, although the formation of an ortho C−N bond theoretically allows an efficient concomitant decarboxylative pathway, this feat has to date only been achieved by Arzoumanidis and Rauch and led to mixtures of compounds that are difficult to separate.…”
Section: C−n Bond Formationmentioning
confidence: 99%
“…20,21 Known methods for the aromatic decarboxylative functionalization usually require either specialized substrates (i.e., ortho-substituted benzoic acids) 22 or very high temperature. 23,24 Although the Dow phenol process has been well investigated, its reaction conditions are harsh (240− 280 °C) and the yield is very low with a limited scope. Moreover, the newly introduced −OH group in Dow's process is at the ortho position instead of the ipso-substitution of −CO 2 H. 25 In 2021, the Ritter group reported a coppermediated decarboxylative esterification protocol promoted by purple light at mild temperature (35 °C).…”
Section: ■ Introductionmentioning
confidence: 99%